Atmospheric Humidity and Air Temperature Studies in Wheat-poplar Based Agroforestry System - Chauhan, V. K.; Dhiman, R. C. (Indian Forester, 2007)
An investigation was carried out in the winter seasons of years 1996, 1997 and 1999 to study the atmospheric humidity and air temperature during the active growth stages of wheat (Triticum aestivum L.) crop raised under 8m × 8cm, 6m × 4m, 5m × 5m and 4m × 6m spacings of poplar (Populus deltoides Marsh.) trees. Height, dbh, crown width and crown length of the trees were significantly higher in tree spaced at 8m × 3m when compared with other spacing. Tree spacing significantly influenced atmospheric humidity and air temperature in wheat crop grown underneath poplar. Atmospheric humidity was directly proportional to within row spacing of trees while air temperature showed the inverse relation. Variation among wheat varieties were significant for both microclimatic parameters throughout the cropping period except for atmospheric humidity during jointing stage (11.00 hours) of crop growth. Interaction effects of tree spacing and crop varieties could not influence significantly both these parameters during the entire growth period of wheat crop.